The Effect of Depreciation of the Exchange Rate on the Trade Balance of Albania - Safet Kurtović (Review of Economic Perspectives, 2017)
Almost all countries face the problems of trade balance, although they are more inherent in developing countries and economies in transition. A majority of economists adheres to a common opinion real depreciation may lead to an improvement of the trade balance. That said, countries encountering trade balance issues use real exchange rate depreciation in order to improve the trade balance situation. Albania belongs to the group of transition countries that has been facing negative trade balance over last two decades. National currency devaluations of the lek (ALL) have been used by Albania to improve its trade balance. Therefore, this paper intends to investigate the effect of the real effective exchange rate depreciation of the ALL on the trade balance of Albania using quarterly data from 1994 to 2015. Bounds testing cointegration approach, vector error correction model (VECM) and impulse response were used for empirical analysis. The results of the study show that there exists a long-term cointegration between the real effective exchange rate depreciation and the trade balance. Specifically, real effective exchange rate depreciation positively affects the trade balance of Albania in both the long-run and short-run indicating the weak presence of the J-curve effect. Important recommendations were derived from the results.
Keywords: F14; F30; F31; 330; Cointegration; Elasticity; J-curve; Long-term effect; Short-term effect